THE EFFECT OF CAPITAL STRUCTURE AND LIQUIDITY ON PROFITABILITY IN COMPANIES PT. BINA MITRA ARTANAMI PERIOD 2019-2023 - Yusnaini; Oky Syahputra; Irma Herliza Rizki (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This research aims to determine and analyze the influence of capital structure and liquidity on profitability in PT. Bina Mitra Artanami. This type of research uses quantitative research. The research sample is PT. Bina Mitra Artanami with 60 data. The data analysis method uses multiple linear regression analysis. Based on the results of the t hypothesis test, it can be concluded that capital structure has a significant effect on profitability and liquidity has a significant effect on profitability. Based on the results of the F hypothesis test, it can be concluded that simultaneously/together capital structure and liquidity have a significant effect on the profitability of PT. Bina Mitra Artanami. Based on analysis of the coefficient of determination, the value of the coefficient of determination or Adjusted R-Square is 0.337 or 33.7% of capital structure and liquidity influence profitability, while 66.3% is the influence of other variables not included in this research.